Problem-based learning application in engineering (2010)
Problem-based learning is a pedagogical strategy widely applied in many universities worldwide with the purpose of improving the learning out come of the students who become the center of the process. This paper presents a case report illustrating an experience, its evolving process and subsequent results of a problem-based learning (PBL) application during five semesters in a Process Management and Control course for under graduate programs of Industrial Engineering and Management Engineering in Colombia. The teacher's role and student assessments are critical elements for the evaluation of the PBL implementation process.